PENGEMBANGAN SISTEM AKUISISI DATA KELEMBABAN DAN SUHU DENGAN MENGGUNAKAN SENSOR DHT11 DAN ARDUINO BERBASIS IOT - Kabul Setiya Budi; Yudhiakto Pramudya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Has been developed an acquisition system Ã‚ data of humidity and temperature by using DHT11 censor and Arduino. Data which have been read by censor of DHT11 then processed by Arduino andÃ‚  then sent to a webserver that is thingspeak. To send data to the web server, used ESP8266 moduleÃ¢â‚¬â„¢s to access wifi signal of portable hotspot. Data of censor of DHT11 then presented in thingspeak with graph form. Temperature data read by DHT11 compared to data read by censor of thermocouple vernier. And then calculated value of error reference that is 1,73%.Keywords: Temperature and Humidity, ESP8266, DHT11, Thingspeak